Sensing of mercury ions in Porphyra by Copper @ Gold nanoclusters based ratiometric fluorescent aptasensor. (15th May 2021) - Shi, Yongqiang; Li, Wenting; Feng, Xuping; Lin, Lei; Nie, Pengcheng; Shi, Jiyong; Zou, Xiaobo; He, Yong
Highlights: Fluorescence intensity and color of apt-Cu@Au NCs served as signal reporters of Hg 2+ . The aptasensor shows high sensitivity for Hg 2+ with detection limit of 4.92 nM. A portable colorimetric microsystem was proposed for visual detection of Hg 2+ . The aptasensor exhibited considerable potential for Hg 2+ detection in Porphyra. Abstract: A novel aptamer-modified Copper @ Gold nanoclusters (apt-Cu@Au NCs) based ratiometric fluorescent probe was developed for mercury ions (Hg 2+ ) determination in Porphyra. The apt-Cu@Au NCs were well dispersed in solution without Hg 2+ but combined together for the formation of thymidine–Hg–thymidine structure with the addition of Hg 2+, which further caused the changes in their fluorescence intensities owing to fluorescence resonance energy transfer. Along with that, the changes in fluorescent colors are visible to the naked eye. Accordingly, Hg 2+ were determined ranging from 0.1 to 9.0 μM by fluorescence analysis with the detection limit of 4.92 nM. Moreover, a homemade device utilizing smartphone and microfluidic chip was designed for colorimetric determination of Hg 2+ ranging from 0.5 to 7.0 μM with good portability and usefulness. The proposed methods were used for Hg 2+ detection in Porphyra with the recoveries of 101.83–114.00%, suggesting the considerable potential for evaluating Hg 2+ levels in aquatic products.